Simplified link reliability enhancement schemes for wireless networks - Boon, Hoi Lim; Chong, Eng Tan (IEEE, 2009)
Today's Internet uses the IP protocol suite that was primarily designed for the transport of data and provides best-effort data delivery. Thus, it does not guarantee the quality of voice transmission that is highly sensitive to error and delay. The situation is even more severe in wireless networks which experience even more distortion and attenuation. Therefore, enhancing the voice traffic quality in the wireless network is essentials for users to experience the lowest erroneous voice traffic. The objective of this paper is to propose an enhanced link reliability scheme and a low level frame prioritize scheme where they are able to improve the QoS in voice traffic especially in wireless networks. Each scheme utilized the wireless environment to tackle the time sensitive traffic. The two schemes have been proven to be able to performance well in enhancing voice quality under specified circumstances via network simulations